Enhancing User Privacy Protection on Social Media Platforms: A Comprehensive Analysis of Self-Regulatory and Supervisory Mechanisms - Mitch, Perry (International Journal of Social Sciences and Public Administration, 2024)
This paper provides an in-depth examination of the challenges and opportunities for enhancing user privacy protection on U.S. social media platforms through self-regulatory and supervisory mechanisms. By conducting a comprehensive analysis of Facebook’s privacy practices and the evolving legal and regulatory landscape in the United States, we highlight the importance of effective self-regulation by social media companies, coupled with robust oversight from government agencies, self-regulatory associations, media, users, and other stakeholders. Drawing upon insights from recent research on algorithmic discrimination, blockchain-based security frameworks, cross-domain defect detection, and legal practices, we propose recommendations for strengthening privacy safeguards and fostering a more trustworthy social media ecosystem. Our findings underscore the need for a multi-stakeholder approach that leverages technological innovations, legal reforms, and collaborative governance to address the complex challenges of user privacy in the digital age.